2003
DOI: 10.1016/j.atmosenv.2003.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Indoor pollutant mixing time in an isothermal closed room: an investigation using CFD

Abstract: We report computational fluid dynamics (CFD) predictions of mixing time of a point pulse release of a pollutant in an unventilated mechanically mixed isothermal room. The aims of the study are to determine (1) the adequacy of the standard RANS two-equation (k-ε) turbulence model to predict the mixing times under these conditions, and (2) the extent to which the mixing time is a feature of the room airflow, rather than the source location within the room. CFD simulations modeled the twelve mixing time experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 9 publications
1
26
1
1
Order By: Relevance
“…During point pulse release of pollutants (i.e., sneezing or coughing) well-mixing conditions may not be achieved before the pollutants are ventilated outside the room. By validating their simulation against experiments, Gadgil et al (2003) found that the mixing process depends primarily on the mean airflow in the room and secondarily on the pollutant source location. This finding is in agreement with our results shown in Fig.…”
Section: Transient Simulationsmentioning
confidence: 97%
“…During point pulse release of pollutants (i.e., sneezing or coughing) well-mixing conditions may not be achieved before the pollutants are ventilated outside the room. By validating their simulation against experiments, Gadgil et al (2003) found that the mixing process depends primarily on the mean airflow in the room and secondarily on the pollutant source location. This finding is in agreement with our results shown in Fig.…”
Section: Transient Simulationsmentioning
confidence: 97%
“…Hussein and Kulmala, 2008;Thatcher et al, 2002). Otherwise, spatial variation of indoor aerosol particle concentrations must be taken into account by, for example, utilizing Computational Fluid Dynamic (CFD) models (Hussein et al, 2005b;Gadgil et al, 2003;Feustel, 1999). In practice, the mass-balance equation is easier to adopt in exposure analysis.…”
Section: Indoor Aerosol Modeling E Mass-balance Equationmentioning
confidence: 99%
“…The reason not to choose a larger volume is that both the deposition rate loss coefficient and the ITF are only meaningful under well-mixed condition and it may not hold for a very large volume and (Furtaw et al, 1996;Gadgil et al, 2003) and supermicron particles (Chen et al, 2005). Two air exchange rates 0.2 and 2 hr −1 are chosen to represent low and high values encountered in natural ventilation for buildings (Wallace et al, 2002).…”
Section: Resultsmentioning
confidence: 97%